Type I IFN-related NETosis in ataxia telangiectasia and Artemis deficiency - Gul, Ersin; Sayar, Esra Hazar; Gungor, Bilgi; Eroglu, Fehime Kara; Surucu, Naz; Keles, Sevgi; Guner, Sukru Nail; Findik, Siddika; Alpdundar, Esin; Ayanoglu, Ihsan Cihan; Kayaoglu, Basak; Geckin, Busra Nur; et al. (MOSBY-ELSEVIER, 2018)
Background: Pathological inflammatory syndromes of unknown etiology are commonly observed in ataxia telangiectasia (AT) and Artemis deficiency. Similar inflammatory manifestations also exist in patients with STING-associated vasculopathy in infancy (SAVI). Objective: We sought to test the hypothesis that the inflammation-associated manifestations observed in patients with AT and Artemis deficiency stem from increased type I IFN signature leading to neutrophil-mediated pathological damage. Methods: Cytokine/protein signatures were determined by ELISA, cytometric bead array, or quantitative PCR. Stat1 phosphorylation levels were determined by flow cytometry. DNA species accumulating in the cytosol of patients' cells were quantified microscopically and flow cytometrically. Propensity of isolated polymorhonuclear granulocytes to form neutrophil extracellular traps (NETs) was determined using fluorescence microscopy and picogreen assay. Neutrophil reactive oxygen species levels and mitochondrial stress were assayed using fluorogenic probes, microscopy, and flow cytometry. Results: Type I and III IFNsignatures were elevated in plasma and peripheral blood cells of patients with AT, Artemis deficiency, and SAVI. Chronic IFN production stemmed fromthe accumulation of DNA in the cytoplasm of ATand Artemis-deficient cells. Neutrophils isolated from patients spontaneously produced NETs and displayed indicators of oxidative and mitochondrial stress, supportive of theirNETotic tendencies. Asimilar phenomenonwas also observed in neutrophils from healthy controls exposed to patient plasma samples or exogeneous IFN-alpha. Conclusions: Type I IFN-mediated neutrophil activation and NET formation may contribute to inflammatory manifestations observed in patients with AT, Artemis deficiency, and SAVI. Thus, neutrophils represent a promising target to manage inflammatory syndromes in diseases with active type I IFN signature.
Keywords: Primary immunodeficiencies; autoinflammation; ataxia telangiectasia; Artemis deficiency; type I IFN; interferonopathy; neutrophil extracellular traps; NETosis